1983
DOI: 10.1159/000241707
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Monitoring in Infants with Respiratory Distress Syndrome

Abstract: Heart rate, short-term heart rate variability, long-term heart rate variability (LTV), mean arterial blood pressure and R-to-pulse time were recorded in 28 infants during the acute phase of respiratory distress syndrome (RDS). The patients were classified by a clinical scoring system into three classes related to the severity of the disease. The LTV was initially significantly (p < 0.01) lower in infants with severe RDS (class III) than in those with moderate or mild disease (classes II and I). Only in class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In studies concerning the influence of RDS on HRV, it has been established that RDS predominantly attenuates LF HRV (2,6,7). This could be confirmed by our study.…”
Section: 208supporting
confidence: 90%
See 2 more Smart Citations
“…In studies concerning the influence of RDS on HRV, it has been established that RDS predominantly attenuates LF HRV (2,6,7). This could be confirmed by our study.…”
Section: 208supporting
confidence: 90%
“…For each 3-min period, the mean R-R interval length was calculated. The severity of RDS was scored at each measurement series as class I (mild), I1 (moderate), or I11 (severe), according to Korvenranta et al (7). An overall RDS score was assigned to each infant based on the worst RDS score that was given at least three times (Table 1).…”
Section: Van Ravenswaaij-arts Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of RDS was assessed by a clinical scoring system, as described earlier. 14 With this scoring system, RDS was graded as mild in 5, moderate in 27, and severe in 5 infants. All distressed infants received an infusion (10 mL/ kg) of Ringer's lactate solution (Ringersteril, Medipolar, Oulu, Finland) during the first 2 hours of life and were also infused with dopamine (5 fxg/kg/min) continuously during the first days of life.…”
Section: Methodsmentioning
confidence: 99%
“…76,120,121 An association in infants with RDS between marked fluctuations in arterial blood pressure and fluctuating cerebral blood-flow velocity has been demonstrated; the association between this pattern and intraventricular hemorrhage (IVH) may be mediated as much by alterations on the venous side of the cerebral circulation as by alterations on the arterial side. 122,123 In a study in which a lower coefficient of variation of systolic blood pressure was observed, blood pressure fluctuation actually was lower in infants who developed IVH.…”
Section: Respiratory Supportmentioning
confidence: 99%